2020
DOI: 10.1111/dth.13394
|View full text |Cite
|
Sign up to set email alerts
|

Demodex positive discoid lupus erythematosus: Is it a separate entity or an overlap syndrome?

Abstract: Discoid lupus erythematosus (DLE) is a chronic inflammatory erythematous skin disease that can be triggered by several factors. Rosacea is another skin disease that causes facial redness and tenderness. Demodex mites have been reported in rosacea and DLE patients commonly in the literature. These two diseases can be seen concomitant, mimic each other clinically and share common possible etiologic factors. To assess demodex mite infestation in both clinical and histopathological findings in DLE patients. We ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…6 One of the goals of rosacea treatment is to reduce the density of demodex mites. 6,7 The effect on the decreasing of the demodex mite density with pulse-dye laser (PDL) therapy in rosacea patients was evaluated in a study. 7 There is no study in the literature evaluating the effect of the pro-yellow laser treatment on the demodex mite density on the skin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 One of the goals of rosacea treatment is to reduce the density of demodex mites. 6,7 The effect on the decreasing of the demodex mite density with pulse-dye laser (PDL) therapy in rosacea patients was evaluated in a study. 7 There is no study in the literature evaluating the effect of the pro-yellow laser treatment on the demodex mite density on the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Demodex parasites (Demodex folliculorum and brevis) also play a role in the pathogenesis of rosacea. Demodex infestation is thought to cause stimulation of the cell‐mediated immune response and the emergence of inflammatory lesions by breaking down the hair follicle wall 6 . One of the goals of rosacea treatment is to reduce the density of demodex mites 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A recent study revealed that demodex was detected in 50% of DLE patients. 5 As DLE and rosacea have common features in their etiopathogenesis and clinical presentation, inflammation and exacerbations caused by demodex mites may exacerbate the severity of DLE. 5 Interestingly, in our patient's biopsy specimen, demodex mites were found in the follicular infundibulum (Figure 1f).…”
Section: Facial Discoid Lupus Erythematosus During Dupilumab Treatmen...mentioning
confidence: 99%
“…5 As DLE and rosacea have common features in their etiopathogenesis and clinical presentation, inflammation and exacerbations caused by demodex mites may exacerbate the severity of DLE. 5 Interestingly, in our patient's biopsy specimen, demodex mites were found in the follicular infundibulum (Figure 1f). Thus, we speculate that reduction of IL-4 by dupilumab caused Th1 and Th17 dominance through Th2 impairment (and demodex mites may have contributed), leading to DLE in our case.…”
Section: Facial Discoid Lupus Erythematosus During Dupilumab Treatmen...mentioning
confidence: 99%